Perbedaan Edukasi Pemberian Makan Balita dengan Metode Emotional Demonstration dan Metode Ceramah terhadap Pengetahuan dan Sikap Ibu Balita di RT 06 RW 08 Kelurahan Keputih Kota Surabaya - Mutiarani, Anugrah Linda; Putri, Pratiwi Hariyani; Yuliani, Kartika (Preventia: The Indonesian Journal of Public Health, 2022)
Undernutrition under five years old has a variety of health risks. In Surabaya, the SSGI 2021 report that underweight cases were 16,6 percent. One of the causes of nutritional problems for toddlers is the behavior of mothers in feeding toddlers which will affect the growth and development of toddlers. The right educational method is needed to change behavior, namely Emotional Demonstration (Emo Demo). This study aimed to analyze the differences in emo demo education and lectures on the knowledge and attitudes of mothers in feeding toddlers. The design for this research is quasi-experimental with a Pre-Postest Control Group. The total sample was 30 people, with a division of 15 people as a control group (lecture method) and 15 as the treatment group (emo demo method). Data collection of knowledge and attitudes of mothers of toddlers was carried out before and after educational intervention, namely by pre-test and post-test. The data were processed with SPSS the using Wilcoxon sign rank test. The results showed significant differences in knowledge and attitudes before and after providing education using the emo demo method (p-value is 0.004). There was no difference in knowledge and attitudes before and after providing education using the lecture method (p-value is 0.157).